Are the costs of the business cycle trivially small? Lucas's calculus of hardship and chooser-dependent, nonexpected utility preferences - Greg Hannsgen (Levy Economics Institute of Bard College, 2007)
In his presidential address to the American Economic Association, Robert Lucas claimed that the welfare costs of the business cycle in the United States equaled .05 percent of consumption. His calculation compared the utility of a representative consumer receiving actual per-capita consumption each year with that of a similar consumer receiving the expectation of consumption. To a risk-averse person, the latter path of consumption confers more utility, because it is less volatile. Applying Amartya Sen's chooser-dependent preferences to a nonexpected utility case, I will counter Lucas's claim by arguing that people have different attitudes toward risk that is imposed and risk that is voluntarily taken on, and that policymakers, in carrying out public duties, must use sorts of reasoning different from those used by the optimizing consumers of neoclassical economic theory.
Keywords: E32; E50; D60; D63; D81; 330; costs of the business cycle; non-expected utility preferences; chooser-dependent preferences; Amartya Sen